Job Satisfaction in Business Enterprises in Nepal (The International Research Journal of Management Science, 2016)
The term management is strongly tied with leadership as it pervades as the management functions. The role of leadership in management is so immense that it is only leadership that can earn result or profit in organizations. Employee job satisfaction is an attitude that people have about their job and the organizations in which they perform their jobs. Numerous factors influence job satisfaction, including salaries, fringe benefits, achievements, autonomy, and recognition, communication, working condition, job importance, positive affectivity, job security workplace flexibility and other factors. The primary objective of this study is to examine the nature and magnitude of relationship between leadership styles and job satisfaction prevailing in the various business sectors in Nepal.